2009
DOI: 10.1093/aob/mcp128
|View full text |Cite
|
Sign up to set email alerts
|

New insights into ferritin synthesis and function highlight a link between iron homeostasis and oxidative stress in plants

Abstract: Studies on plant ferritin functions and regulation of their synthesis revealed strong links between these proteins and protection against oxidative stress. In contrast, their putative iron-storage function to furnish iron during various development processes is unlikely to be essential. Ferritins, by buffering iron, exert a fine tuning of the quantity of metal required for metabolic purposes, and help plants to cope with adverse situations, the deleterious effects of which would be amplified if no system had e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
198
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(210 citation statements)
references
References 127 publications
8
198
1
3
Order By: Relevance
“…It has been demonstrated that ferritin plays a crucial role in iron storage in higher plants [35][36][37] and unicellular microalgae. 19,[38][39][40] On the other hand, ferritin contribution to iron storage in macroalgae or seaweeds is explored only recently, 24) although a ferritin gene is described as a stress-induced gene in a green seaweed Ulva sp.…”
Section: Unpublished Data)mentioning
confidence: 99%
“…It has been demonstrated that ferritin plays a crucial role in iron storage in higher plants [35][36][37] and unicellular microalgae. 19,[38][39][40] On the other hand, ferritin contribution to iron storage in macroalgae or seaweeds is explored only recently, 24) although a ferritin gene is described as a stress-induced gene in a green seaweed Ulva sp.…”
Section: Unpublished Data)mentioning
confidence: 99%
“…Ferritin is the intracellular protein responsible for the sequestration, storage and release of iron. There are strong links between ferritins, protection against oxidative stress and coping with adverse conditions (Briat et al, 2009). …”
Section: Genes Showing Higher Expression Patterns In Resting Eggsmentioning
confidence: 99%
“…Besides a role as a putative Fe-storage protein, studies on plant ferritin functions have indicated a probable link between this protein and protection against oxidative stress (Briat et al 2010b). Ferritin in animals has also been documented to bind Al atoms, which might be a cellular protection mechanism, guarding against eventual accumulated oxidative damage (Sakamoto et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is a protein found in all the living kingdom, except in yeast, that can store up to 4,500 iron (Fe) atoms in their central cavities (Briat et al 2010b). In animal cells, ferritin is involved in the response against stresses resulting from ultraviolet irradiation, phorone (a glutathione-depleting drug), and excess iron (Vile & Tyrrell 1993, Cairo et al 1995, Déak et al 1999.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation